Influence of cavity lifetime on high-finesse microcavity two-photon absorption photodetectors - Donegan, John; Bradley, Louise (My University, 2007)
For optical pulse incidence as compared with continuous-wave incidence, the enhancement of two-photon absorption inside a high-finesse planar microcavity is reduced, the pulse inside the cavity and the cavity spectrum are broadened. The analysis shows that for transform-limited pulse incidence, the true pulsewidth and the cavity frequency resolution can be estimated if the cavity lifetime or the cavity bandwidth has been obtained from the reflection or transmission spectrum of the cavity.
PUBLISHED
Keywords: Optics; light refelction; micro-optics